BREAST CARE FOR BREASTFEEDING PREPARATION DURING THE COVID-19 PANDEMIC IN JOHAR BARU VILLAGE 2 - Utami, Yosefin Beni Purbo (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
The COVID-19 pandemic has limited face-to-face health education, including for pregnant women who need information about breastfeeding preparation. One important aspect of successful breastfeeding is breast care during pregnancy. This community service activity aims to increase pregnant women's knowledge about breast care in preparation for breastfeeding through online counseling. The activity was carried out in Johar Baru Village, Central Jakarta, targeting 9 pregnant women. The activity methods included counseling through Zoom Cloud Meeting and mentoring through WhatsApp Group. Evaluation was conducted using pre-tests and post-tests to measure the increase in participants' knowledge. The results of the activity showed a significant increase in the level of knowledge of pregnant women, with an average pre-test score of 61.1 and a post-test score of 87.8, representing an increase of 43.7%. Participants gained a better understanding of proper breast care techniques and their benefits in facilitating milk production and preventing lactation disorders. This online counseling activity proved to be effective in increasing the knowledge of pregnant women and became an alternative form of practical health education during the pandemic. It is hoped that similar activities can be carried out continuously to support the success of the exclusive breastfeeding program and improve the quality of health of mothers and babies in the community.